Cadaveric Anatomic Study of Pituitary Stalk Mobilization: Implications for Neurosurgery - Altunyuva, Oguz; Kasab, Reyhan; Fedakar, Recep; Yilmazlar, Selcuk (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Surgical intervention in the subchiasmal region is complex due to the presence of critical neurovascular structures. This study aimed to elucidate the detailed anatomy of this region and identify safe surgical mobilization techniques.Eight cadaveric specimens underwent anatomical dissection to examine the subchiasmal region, its neurovascular components, and skull base structures. The supportive structures of the pituitary stalk were meticulously exposed to assess its mobility.During dissection of the arachnoid membranes surrounding the pituitary stalk, two distinct, thick arachnoid bands were identified enveloping the stalk and superior hypophyseal arteries. These bands were situated within the inner layer of the arachnoid membranes, forming a funnel-like structure that enclosed and protected the pituitary stalk. These bands originated from the inferior aspects of the bilateral optic nerves and extended medially from both internal carotid arteries.The internal arachnoid bands identified in our study encase and protected the superior hypophyseal arteries. By stabilizing the pituitary stalk and preserving pituitary gland perfusion, these bands may act as a protective mechanism against neuroendocrine complications, such as diabetes insipidus, particularly in mild to moderate head trauma.
Keywords: skull base; subchiasmal region; arachnoid bands; surgical mobilization; pituitary